Blood and oranges : European markets and immigrant labor in rural Greece - Lawrence, Christopher M. (Dislocations, 2007)
A compelling account of the intersection of globalization and neo-racism in a rural Greek community, this book describes the contradictory political and economic development of the Greek countryside since its incorporation into the European Union, where increased prosperity and social liberalization have been accompanied by the creation of a vulnerable and marginalized class of immigrant laborers. The author analyzes the paradoxical resurgence of ethnic nationalism and neo-racism that has grown in the wake of European unification and addresses key issues of racism, neoliberalism and nationa.